High antibacterial properties of green synthesized gold nanoparticles using Uncaria gambir Roxb. leaf extract and triethanolamine - Syukri Arief, Fri Wardana Nasution, Zulhadjri, Arniati Labanni (Journal of Applied Pharmaceutical Science, 2020)
The development of antibacterial agents is increasingly gaining much attention due to the expansion activity of multi-drug resistant bacteria in causing many diseases. Metallic nanoparticles especially gold nanoparticles in the field of nanotechnology is one of the new and significant materials to be developed as antibacterial agents. Gold nanoparticles have been successfully synthesized using Uncaria gambir Roxb. leaf extract as a bioreducing agent and triethanolamine as a capping agent, through reduction of Au+3 by flavonoid compound in the leaf extract. The effect of triethanolamine and hydrogen tetrachloroaurate (III) acid concentration on the stability and size of nanoparticles was studied. The presence of triethanolamine 1% as a capping agent successfully maintained the stability of colloidal gold nanoparticles with a concentration of hydrogen tetrachloroaurate (III) acid at 100 ppm. X-Ray Diffraction analysis showed peak patterns corresponding to the metallic gold standard with a crystallite size of 32.52 nm. Transmission Electron Microscope analysis showed that particles were spherical, hexagonal, and triangular, where the smallest particle size was 7 nm. Synthesized gold nanoparticles showed great antibacterial activity against E. coli and S. aureus. The stability and antibacterial activity of synthesized gold nanoparticles showed good potential to be developed in biomedical applications.
Keywords: Green synthesis, gold nanoparticles, Uncaria gambir Roxb., triethanolamine, biomedical applications, bioreducing agent.